2006
DOI: 10.1074/jbc.m608158200
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Segment 12 of the Glut1 Glucose Transporter Is an Outer Helix and Is Not Directly Involved in the Transport Mechanism

Abstract: A model has been proposed for the exofacial configuration of the Glut1 glucose transporter in which eight transmembrane domains form an inner helical bundle stabilized by four outer helices. The role of transmembrane segment 12, predicted to be an outer helix in this hypothetical model, was examined by cysteine-scanning mutagenesis and the substituted cysteine accessibility method using the membrane-impermeant, sulfhydrylspecific reagent, p-chloromercuribenzenesulfonate (pCMBS). A previously characterized func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
6
29
0
Order By: Relevance
“…153 and Lys 183 (this study), the unexpected accessibility of mutants Q161C and I164C of TM5 to interstitial 4-(chloromercuri)benzosulfonic acid (10), and the SDS-dependent accessibility of Arg 153 and Lys 183 (this study). TM12 adjustment to relocate Lys 451 one additional helix turn into the lipid bilayer (direction cytoplasm to interstitium) would explain the trypsin inaccessibility of Lys 451 (this study) and, by displacing N-terminal TM12 sequence into the interstitium, may also explain the unexpected accessibility of TM12 Y432C through I436C to interstitial 4-(chloromercuri)benzosulfonic acid (10). These interpretations must be tempered by the possibility of residue occlusion by local structure.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…153 and Lys 183 (this study), the unexpected accessibility of mutants Q161C and I164C of TM5 to interstitial 4-(chloromercuri)benzosulfonic acid (10), and the SDS-dependent accessibility of Arg 153 and Lys 183 (this study). TM12 adjustment to relocate Lys 451 one additional helix turn into the lipid bilayer (direction cytoplasm to interstitium) would explain the trypsin inaccessibility of Lys 451 (this study) and, by displacing N-terminal TM12 sequence into the interstitium, may also explain the unexpected accessibility of TM12 Y432C through I436C to interstitial 4-(chloromercuri)benzosulfonic acid (10). These interpretations must be tempered by the possibility of residue occlusion by local structure.…”
Section: Discussionmentioning
confidence: 61%
“…Homology modeling suggests involvement of GLUT1 TMs 2, 4, 5, 7, 8, and 10 in substrate binding (11), although caveats with this approach have been noted (22). Scanning cysteine mutagenesis implicates GLUT1 TMs 1, 5, 7, 8, and 11 in sugar binding (10). (19), which form the cytoplasmic loop and TM segments of the TM10-TM11 hairpin (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45,62,63 Cysteine scanning mutagenesis was subsequently employed to probe which residues lined this proposed central pore. [64][65][66][67][68][69][70][71][72][73][74] The resulting model indicated that TMs 2, 4, 5, 7, 8, 11, and possibly 1 and 10 formed a central aqueous transport channel for glucose, whereas TMs 3, 6, 9, and 12 formed a structural scaffold on the outside of the protein. 70 A possible substrate binding site was also proposed, involving Q161, Q282, and W412.…”
Section: Structure Of Human Glut1mentioning
confidence: 99%
“…(online first, page number not for citation purpose) crease in the expression of glucose transporter in lung cancer and thymic epithelial tumors [18,29] . A higher expression of SGLT1 has also been found in ovarian, colorectal, and lung cancer tissues compared to healthy tissues, indicating a positive correlation between the activity of glucose transporters and tumor development [30] .…”
Section: Expression Of Glucose Transporters In Tumor Cellsmentioning
confidence: 99%